2019
DOI: 10.1088/1755-1315/400/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Present Climate Developments in Southern Siberia (1963-2017 years)

Abstract: Siberia is a key region for mapping the climate development in north-central Eurasia in terms of global climatic change. The territorial relief creates a major orographic barrier for atmospheric streams influencing the regional altitudinal weather zonality. Systematic 55-year (1963-2017) weather observations along the 700 km N-S latitudinal transect across the southern Siberian plains and the adjoining ranges of the Altai-Sayan Mountains document progressing seasonal temperature and humidity shifts. Regionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Over the period of instrumental satellite observations (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), Ponomarev et al (2016) reported that a logarithmic growth in the number of burnt areas and fire frequency was found for forest, steppe, and forest steppe zones as in other parts of Siberia. The current climate warming observed in southern Siberia is most evident in the alpine zone of the Altai and Sayan Mountains (Kharlamova et al 2019) and is leading to aridification of the mountain steppes, altitudinal tree-line migration and restructuring of mountain biotopes (Chlachula 2005). The climate is predicted to become much drier than today in the southern part of the Altai-Sayan mountains, resulting in drastically decreasing extents of mountain biomes including alpine, alpine tundra, and subalpine plant communities (Kokorin 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over the period of instrumental satellite observations (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), Ponomarev et al (2016) reported that a logarithmic growth in the number of burnt areas and fire frequency was found for forest, steppe, and forest steppe zones as in other parts of Siberia. The current climate warming observed in southern Siberia is most evident in the alpine zone of the Altai and Sayan Mountains (Kharlamova et al 2019) and is leading to aridification of the mountain steppes, altitudinal tree-line migration and restructuring of mountain biotopes (Chlachula 2005). The climate is predicted to become much drier than today in the southern part of the Altai-Sayan mountains, resulting in drastically decreasing extents of mountain biomes including alpine, alpine tundra, and subalpine plant communities (Kokorin 2011).…”
Section: Introductionmentioning
confidence: 99%